Antimicrobial activity of aloe-emodin from Aloe-vera against Staphylococcus aureus - Ola Salam Znad,; Zainab Razzaq Zghair, (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the antibacterial activity of aloe-emodin isolated from aloe-vera against staphylococcus aureus from human patients and cows suffering from respiratory tract infection. Method: The experimental study was conducted at the A;-Kut Technical Institute, Iraq, from October 2021 to December 2021, and comprised human nasal swabs collected from Al-Zahraa Teaching Hospital and Al-Karama Teaching Hospital in Wassit, Iraq, in group A, cow nasal swabs collected from city centre, Al-Hay, Al-Bataar, Sheikh Saad, Al-Azizia and Al- Suwaira fields in group B. Aloe-vera was taken from the local market for which certification was obtained from the Directorate of Seed Testing and Certification, Ministry of the Agriculture, Iraq. The swab specimens were transferred to the laboratory under standard conditions. The specimens were inoculated to mannitol salt agar and blood agar media and were then incubated for 24-48hrs at 37°C under aerobic conditions. All the primary screened isolates were then subjected to various morphological and biochemical tests to ensure their identity. Data was analysed using the statistical analysis system, 2018. Results: Of the 200 samples, 100(50%) were in group A and 100 100(50%) in group B. Aloe-emodin was the most effective antibiotic that inhibited human and cow pathogenic bacteria with high inhibition zone range at (1%) which increased with increasing aloe-emodin extract concentrations at (2% ,4%). Staphylococcus isolates revealed a different response to the aloe-emodin antimicrobial activity. Conclusion: Aloe-emodin extract of alo-vera showed high antimicrobial activity against all human and cow pathogenic bacteria. Keywords: Cattle, Aloe, Emodin, Plant, Anti-bacterial, Anti-infective, Nose, Agriculture, Ethanol, Seeds.